Sovereignty and Responsibility Power, Norms and Intervention in International Relations - Moses, J. (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2014)
This book is a critical study of the concept of sovereignty and its relationship to responsibility. It establishes a clear distinction between empirical and normative definitions of sovereignty and examines the implications of these concepts in relation to intervention, international law, and the world state.